FAKTOR-FAKTOR KARAKTERISTIK PERAWAT DALAM MELAKSANAKAN DOKUMENTASI ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RUMAH SAKIT MITRA KASIH - Sumiati, Pipit; Suryani, Melyati (LPPM Akper Kebonjati, 2025)
This study aims to determine the external factors in the implementation of nursing care documentation in the inpatient room of Mitra Kasih Cimahi Hospital. This study used a quantitative descriptive design, involving some nurses in the inpatient room of 37 respondents and 37 nursing care documentation. Results. The results showed that 37 nurses (100%) who performed nursing care documentation were included in the early adulthood category with most of the 33 people (89.2%) having a D3 Nursing education, 20 people (54.1%) had a good level of knowledge, 19 people (51.4%) had a positive attitude, 25 people (67.6%) had moderate motivation, and 19 people (51.4%) did complete documentation. There is regular evaluation with standardized standards and feedback so that nurses know the successes and shortcomings in writing and feel cared for by superiors directly.